تفسیر مواہب الرحمٰن کے امتیازی پہلو: Distinctive Aspects of Tafsīr Mawāḥib al-Raḥmān (Al-Qamar, 2020)
Syed Amīr ̒Alī Maīh Ābādī is one of the leading scholars of Tafsīr of the Quran in the subcontinent. His Tafsīr known as “Mawāḥib al-Raḥmān” is a big achievement in the relevant field. The author of this article has conducted research about referred Tafsīr from two aspects, in brief, to obtain the higher study degree, the author has carried out his M. Phil degree thesis from International Islamic University Islamabad and covered its one aspect “Manhaj al-Tafsīr” and then to cover its jurisprudential aspects. The author presented his dissertation of PhD in Mohi ud Din Islamic University. Due to the substantial working on this particular subject, he had the opportunity to study this Tafsīr and it enhanced the eagerness of the author of this article. During the study of this Tafsīr, the author came across distinctive aspects of this Tafsīr. One of them is, though all the writers of Tafsīr have already written down on all the related subjects which are the supportive in Tafsīr of the verses of the Quran and either the foremost but apart form that Syed Amīr ̒Alī kept the focus on the some particular subjects of the Quran. He explained this thing in the preface of the Tafsīr that some important aspects of the Quran were mainly focused and he also explicated the rationale and his own interest for it and he unequivocally explained that he considered the fourteen aspects while doing Tafsīr. An attempt is made in this article to highlight the fourteen points and the aspects of the author of this Tafsīr that he particularly focused on these aspects and to explain the importance of those points.
Keywords: Amīr ̒Alī; Tafsīr; Mawāhib al-Rehmān; features